Dampak Pemberian Es Krim Buah Bit dan Jambu Biji Merah terhadap Kadar Haemoglobin Remaja Putri - Nurlaela Sari, Dewi; Mulyani, Yanyan; Ariani, Antri (Jurnal Kesehatan Komunitas, 2024)
The emergence of nutritional problems in children is closely related to the preparation of a woman's health and nutrition to become a prospective mother, in this case, a young woman. The results of the Nutrition International survey in 2018 found cases of anemia in young women in West Java by 41.93%, this is in line with the target coverage of giving blood-added tablets to adolescent girls which is still low (25.2%) and still below the target of West Java. (52%). Intervention efforts are needed to prevent anemia by optimizing the provision of iron-containing foods in addition to giving blood-added tablets. The purpose of this research is to determine the effect of beetroot ice cream and red guava on the hemoglobin levels of adolescent girls. The method used is a quasi-experimental approach with a one-group pre-post design approach. The sample in this study was 30 respondents with a purposive sampling technique with inclusion criteria of mild and moderate anemia who did not suffer from a disease that could cause anemia. Determination of anemia by measuring hemoglobin levels using the POCT (Point of Care Testing) method. The analysis technique uses frequency distribution, normality test, and bivariate test using the Wilcoxon test through SPSS computer software. The results showed that all respondents (100%) had mild anemia before being given beetroot and red guava ice cream. There is a significant change with p-value 0.000 < alpha value (0.05). It can be concluded that giving beetroot ice cream and red guava if consumed regularly and appropriately can reduce the incidence of anemia, so it is hoped that this can be used as a policy toward intervention in adolescent girls with anemia.